Penyuluhan Hukum Mengenai Perlindungan Anak Jalanan Perempuan di Kota Bandung - Imas Rosidawati; Nani Kurniasih (LPPM UNINUS, 2011)
Homeless Children in Bandung is a social problem that is being widely observed by all parties, both government and civil society/NGOs. Legal counseling is done at the shelter organizer in this case Yayasan Bahtera, which specifically deals with the existence of homeless children, the issue that interest people is girls though in terms of quantitatively less than boys since girls are particularly vulnerable by various acts of other behavior sides. The existence of homeless girls has also many aspects related to the problem of morality and law, even at serious principle things related to sexual crimes, such as persuasion, violation, prostitution and trafficking. Therefore, the law is intended to give more understanding of legal protection